Pembelajaran Berdiferensiasi pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Negeri 8 Purwokerto - Sidqi Amalul Azmi, Sabrina; Rohman, Mujibur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Diversity in characteristics, learning styles, and students' backgroundsis an important aspect that every educator must deeply understand. This is due tothe fact that each individual has a unique way of learning that cannot begeneralized. Therefore, educators are required to design differentiatedinstruction in the classroom. This approach aims to tailor the learning process tothe needs, characteristics, and learning styles of each student, so they can gain amore meaningful learning experience. This study aims to describe theimplementation of Differentiated Instruction in the Islamic Religious Educationsubject at SMP Negeri 8 Purwokerto. The researcher used a qualitative researchmethod with a descriptive approach. Data were collected through observation,interviews, and documentation, while the data analysis techniques included datareduction, data presentation, and drawing conclusions. The results of the studyinclude the initial assessment conducted by educators to group students based ontheir learning styles and abilities, the implementation of differentiated instructionwhich consists of three aspects differentiation of content, process, product.Evaluation conducted after the differentiated learning. This effort is made so thatthe learning strategies designed are truly able to accommodate the diverseneeds, potential, and learning styles of students.